Tabayag lime containers of the Cordilleras - Tysmans, Wig; Quintos, Floy C. (Bencab Art Foundation, 2006)
This book is fully illustrated. A collector's item. "Each of the pieces featured in this book is an expression of the genius of the Cordillera people, and a work of genuine Filipino art." - Bencab 'In a hyper-modern world where every ephemeral subculture springing from every obscure subgroup gets scrutinized and, eventually sprung on the world at large via the omniscient web, the thrill of discovering something totally new and heretofore unexamined is something to be savored. It is this peculiar excitement that Filipino National Artist Bencab hopes to share in Tabayag: Lime Containers of the Cordilleras.'